Global Perspectives on Design Science Research 5th International Conference, DESRIST 2010, St. Gallen, Switzerland, June 4-5, 2010. Proceedings. - Winter, Robert.; Zhao, J. Leon.; Aier, Stephan. (Lecture Notes in Computer Science,, 2010)
This book constitutes the refereed proceedings of the 5th International Conference on Global Perspectives on Design Science Research, DERIST 2010, held in St. Gallen, Switzerland, in June 2010. The 35 revised full papers presented together with 10 revised short papers were carefully reviewed and selected from 80 submissions. The papers are organized in topical sections on organising design research, reflecting design science research, design research techniques, design and context, design and organisation, design and information, design research exemplars, design and behaviour, designing collaboration, as well as design and requirements engineering.